A análise documentária como forma de evitar o apagamento do patrimônio bibliográfico de C&T: as teses da Faculdade de Medicina do Rio de Janeiro do século XIX - Conceição, Algacilda Alves da (2023)
Based on a practical methodological approach, this paper discusses thematic indexing in the rare theses of the FMRJ. Its general objective is to recommend guidelines for the Indexing Policy of the Library and Information System of the Federal University of Rio de Janeiro for rare theses, which constitutes its technical scientific product. It starts from the assumptions that inadequate or insufficient indexing can lead to the erasure and forgetfulness of this S&T bibliographic heritage, promoting the loss of information about the materiality of these works, decreasing the value of the collection as well as hindering subsidies for its preservation. From these premises, this research proposes as a model the use of DeCS for subjects related to the Health area and the creation of a glossary to standardize the information in the Content Notes and Summary, indicating the preservation of these works, used by the first generations of doctors trained at the Faculty of Medicine of Rio de Janeiro.